Synthesis, Characterization, and Antimicrobial Activity of Near-IR Photoactive Functionalized Gold Multibranched Nanoparticles - Kalachyova, Yevgeniya; Olshtrem, Anasiya; Guselnikova, Olga A; Postnikov, Pavel S; Elashnikov, Roman; Ulbrich, Pavel; Rimpelová, Silvie; Švorčík, Václav; Lyutakov, Oleksiy (ChemistryOpen, 2017)
Surface-modified gold multibranched nanoparticles (AuMs) were prepared by simple chemical reduction of gold chloride aqueous solution followed by in situ modification by using water-soluble arenediazonium tosylates with different functional organic groups. Chemical and morphological structures of the prepared nanoparticles were examined by using transmission electron and scanning electron microscopies. The covalent grafting of organic compounds was confirmed by scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM-EDX) and Raman spectroscopy techniques. Covalent functionalization of nanoparticles significantly expands the range of their potential uses under physiological conditions, compared with traditional non-covalent or thiol-based approaches. The antibacterial effect of the surface-modified AuMs was evaluated by using Escherichia coli and Staphylococcus epidermidis bacteria under IR light illumination and without external triggering. Strong plasmon resonance on the AuMs cups leads to significant reduction of the light power needed kill bacteria under the mild conditions of continuous illumination. The effect of the surface-modified AuMs on the light-induced antibacterial activities was founded to be dependent on the grafted organic functional groups.
Keywords: infračervené záření; kovové nanočástice; spektrometrie rentgenová emisní; zlato; Anti-Infective Agents; Spectrometry, X-Ray Emission; Microscopy; Infrared Rays; Surface Properties; povrchové vlastnosti; antiinfekční látky; mikroskopie; Metal Nanoparticles; Gold